Study on Mathematical Model for Condensation Heat Transfer in Two-phase Closed Thermosyphon. Issue 1 (August 2020) - Ren, Bin; Pu, Zhe; Du, Yannan; Tang, Xiaoying; Yang, Yuqing; Lu, Hongliang
Abstract: The two-phase closed thermosyphon is a special heat pipe utilizing gravity instead of capillary force to return the liquid to evaporator. Some assumptions for Nusselt model are not true in the condenser section, resulting in the complexity of condensation. In this paper, a numerical model based on Nusselt's model is developed considering vapour-liquid interfacial shear stress. The distributions of local parameters such as shear stress, liquid film thickness are analysed. The variation of average heat transfer coefficient with temperature difference is displayed. And the average heat transfer coefficients predicted by numerical model are compared with values calculated from other references. The results show that both the shear stress and liquid film thickness increase as condensation proceeds. But the growth rate decreases along the axial direction. The average heat transfer coefficients predicted by this model is lower than that calculated by Nusselt's correlation especially at higher heat load, indicating that shear stress really reduces the heat transfer performance.